Evaluasi Lingkungan Belajar Klinik dan Kepuasan Mahasiswa Keperawatan Terhadap Pembelajaran Klinik - Sinta Fresia; Imelda Avia; Nur Afni Wulandari Arifin; Wahyuni Dwi Rahayu; Sri Kurnia Dewi (Universitas Malahayati Lampung, 2026)
ABSTRACT The clinical learning environment is a crucial element in nursing education that plays an important role in developing the professional competence of Nursing Students. The clinical practice environment includes interactions between Nursing Students, health workers, patients, and access to facilities and resources that support learning. The purpose of this study was to analyze the relationship between the evaluation of the clinical learning environment which includes the clinical learning environment, leadership style, care in the room and the role of clinical Perceptorship associated with the satisfaction of Third Grade Nursing Students towards clinical learning at RSAU which includes satisfaction with provisioning and reflection as well as satisfaction with clinical reasoning experiences. This study used quantitative research methods and data analysis used were univariate and bivariate with Chi Square statistical tests. Respondents were 57 Nursing Students of Level III Nursing Diploma study program who had completed field clinical practice at the Air Force Hospital dr. Esnawan Antariksa. Sample collection used a total sampling technique. Research Results Based on the analysis obtained from data processing The results of the bivariate test obtained p-value = 0.000 0.05, indicating that Ho was rejected, it was concluded that there was a relationship between the implementation of clinical learning evaluation and student satisfaction in clinical learning. This study is expected to be beneficial for Hospital institutions as a place for clinical practice and the community, so that it can improve the quality of the clinical learning environment and improve learning renewal methods in the appropriate clinical environment for Nursing Students. Keywords: Evaluation of the Clinical Learning Environment, Student Satisfaction and Clinical Learning. ABSTRAK Lingkungan belajar klinik adalah elemen krusial dalam pendidikan keperawatan yang memainkan peran penting dalam mengembangkan kompetensi profesional Mahasiswa Keperawatan. Lingkungan praktik klinik mencakup interaksi antara Mahasiswa Keperawatan, tenaga kesehatan, pasien, serta akses ke fasilitas dan sumber daya yang mendukung pembelajaran. Tujuan penelitian ini adalah untuk menganalisa Hubungan evaluasi lingkungan belajar klinik yang meliputi lingkungan belajar klinik, gaya kepemimpinan, perawatan di ruangan dan peran Perseptorship klinik dihubungkan dengan kepuasan Mahasiswa Keperawatan TK III terhadap pembelajaran klinik di RSAU yang meliputi kepuasan terhadap pembekalan dan refleksi serta kepuasan terhadap pengalaman penalaran klinis. Penelitian ini menggunakan metode penelitian kuantitatif dan Analisa data yang digunakan yaitu univariat dan bivariat dengan uji statistik Chi Square. Responden merupakan Mahasiswa Keperawatan program studi Diploma keperawatan Tingkat III sejumlah 57 orang yang telah menyelesaikan praktek klinik lapangan di Rumah Sakit Angkatan Udara dr. Esnawan Antariksa. Pengumpulan sampel menggunakan teknik total sampling. Hasil Penelitian Berdasarkan analisis diperolehhasil pengolahan data Hasil uji bivariat diperoleh p-value = 0.000 0.05, menunjukan bahwa Ho ditolak, disimpulkanbahwa terdapat hubungan adanya pelaksanaan evaluasi pembelajaran klinik dan kepuasan mahasiswa dalam pembelajaran klinik. Penelitian ini diharapkan dapat bermanfaat bagi institusi Rumah Sakit sebagai lahan praktik klinik dan masyarakat, sehingga dapat meningkatkan kualitas lingkungan belajar klinik serta meningkatkan metode pembaharuan pembelajaran di lingkungan klinik yang tepat bagi Mahasiswa Keperawatan. Kata Kunci: Evaluasi Lingkungan Belajar Klinik, Kepuasan Mahasiswa dan pembelajaran Klinik.